(untitled) (XXI Century. Spanish Literature and Culture, 2024)
This essay will explore how some of Spain’s 21st century female playwrights address pressing global issues including historical memory, the climate crisis, the dehumanizing effects of forced migration, race and colonialism, the disappearance of the remaining vestiges of humanity, and female agency. Through a powerful blend of content and form, the playwrights capture the urgency of the present moment and inspire their audiences to take stock of their apathy and become more actively involved in needed social change.